An efficient, three-dimensional non-fullerene electron acceptor: functionalizing tetraphenylethylene with naphthalene diimides. (7th May 2019) - Wagalgave, Sopan M.; Bhosale, Sheshanath V.; Bhosale, Rajesh S.; Puyad, Avinash L.; Chen, Jing-Yu; Li, Jing-Liang; Evans, Richard A.; Gupta, Akhil; Bhosale, Sidhanath V.
Abstract : A non-fullerene acceptor, W8, based on tetraphenylethylene and naphthalene diimide ITO/PEDOT:PSS/PTB7:W8 (1 : 1.2 D : A w/w)/Ca/Al; PCE = 8.58%. Abstract : A tetraphenylethylene-functionalized, three-dimensional non-fullerene electron acceptor, 9, 9′, 9′′, 9′′′-(ethene-1, 1, 2, 2-tetrayltetrakis(benzene-4, 1-diyl))tetrakis(4-(4-methylpiperidin-1-yl)-2, 7-dioctylbenzo[ lmn ][3, 8]phenanthroline-1, 3, 6, 8(2 H, 7 H )-tetraone) (coded asW8 ), which used naphthalene diimide units as terminal functionalities, was designed, synthesized and characterized. It was highly soluble ( i.e. >20 mg mL −1 in o -dichlorobenzene), thermally stable, and exhibited energy levels complementing those of the commonly used donor polymers, P3HT and PTB7. Not only isW8 the first reported example in the literature that comprises tetraphenylethylene and naphthalene diimide building blocks, but the device performances [D : A 1 : 1.2 = 5.26% (P3HT); 8.58% (PTB7)] outlined herein are among the best in the investigated class of three-dimensional non-fullerene electron acceptors.